From schlemiel to sabra : Zionist masculinity and Palestinian Hebrew literature - Hollander, Philip (Perspectives on Israel studies, 2019)
"In From Schlemiel to Sabra Philip Hollander examines how masculine ideals and images of the new Hebrew man shaped the Israeli state. In this innovative book, Hollander uncovers the complex relationship that Jews had with masculinity, interrogating narratives depicting masculinity in the new state as a transition from weak, feminized schlemiels to robust, muscular, and rugged Israelis. Turning to key literary texts by S. Y. Agnon, Y. H. Brenner, L. A. Arieli, and Aharon Reuveni, Hollander reveals how gender and sexuality were intertwined to promote a specific Zionist political agenda. A Zionist masculinity grounded in military prowess could not only protect the new state but also ensure its procreative needs and future. Self-awareness, physical power, fierce loyalty to the State and devotion to the land, humility, and nurture of the young were essential qualities that needed to be cultivated in migrants to the State. By turning to the early literature of Zionist Palestine, Hollander shows how Jews strove to construct a better Jewish future"--